Predictors of Recovery Rate in Treatment of Children with Severe Acute Malnutrition Using Outpatient Therapeutic Feeding Program in Shalla District, South West Ethiopia - Sultan Husen; Jeylan Esmael; Adem Abdulkadir Abdi; Mustafa Ansha (International Journal of Nutrition Sciences, 2022)
Background: Recovery rate of children with severe acute malnutrition can be affected by several factors. The study accentuated on identifying recovery rate and its predictors in treatment of children with severe acute malnutrition using Outpatient Therapeutic Feeding Program in Shalla Health District, South West Ethiopia.Methods: Institutional based retrospective cohort study design was employed. A record of 1004 was collected and analyzed. Kaplan Meier procedure, Log rank test and multiple variable cox proportional hazard regression were used in order to test the significant relationship between recovery rate and independent factors.Results: The finding of the study revealed that 90.9% of children recovered with a median recovery time of 45 days with an interquartile range (IQR) from 5 to 7 weeks. The recovery rate among those who received amoxicillin was 5.86 (Adjusted Hazard Ratio (AHR)=5.86, 95% CI: 4.55-7.55) times higher than those who did not receive. Additionally, the finding of the study showed that the recovery rate of children who had diarrhea was 49% (AHR=0.51, 95% CI: 0.44-0.59), vomiting was 61% (AHR=0.39, 95% CI: 0.33-0.46), and among those who were admittedwith edema was 30% (AHR=0.70, 95% CI: 0.58-0.84) that were less likely than those admitted without edema.Conclusion: It was identified that medication with amoxicillin was taken as a predicator that positively affected the time to recover. But; diarrhea, vomiting and edema were recognized as factors affecting recovery time negatively. Thus, early identification and management of diarrhea, vomiting and edema as well as regular management of cases with antibiotics is recommended to improve recovery rate.